GAYA BELAJAR MAHASISWA YANG BEKERJA: PENELITIAN DI STKIP PURNAMA JAKARTA - Damanik, Jafriansen (Jurnal Dinamika Pendidikan, 2015)
Oneâs ability to absorb and master the subject matter is different from one another. Some are able to learn quickly, some other are slow. This may be caused by the learning styles and also some aspects both from within and from outside. The purpose of this study was to find out what learning styles adopted by the students of STKIP Purnama, especially those who already work in both at school and in other institutions and also to identify the factors that influence the studentsâ learning activities. This research method applied were observation, interview, and documentation. The results showed that learning style that is applied by students STKIP Purnama, especially those who already work, is the auditory and visual learning styles. A total of 15 respondents applying auditory learning style, while 5 respondents applying visual learning style.Keywords : learning materials, learning style